Neglected knee dislocation with osteoarthritis managed by total knee replacement: A case report (Indian Journal of Case Reports, 2025)
This case report presents a 50-year-old male with chronic, untreated knee dislocation complicated by end-stage osteoarthritis (OA), following a traumatic injury a year prior. The patient presented with left knee pain, swelling, and restricted mobility. Radiographs confirmed joint degeneration and knee dislocation. Total knee replacement (TKR) was performed to address both degenerative changes and joint instability. The surgery proceeded without complications, and post-operative care included multimodal pain management, antibiotics, and structured physiotherapy. The patient experienced significant improvement in mobility, gait, and overall quality of life, with no post-operative issues. This case underscores the need to consider neglected joint injuries in chronic cases and demonstrates how timely surgical intervention, particularly TKR, can restore function in complex OA presentations. It also highlights the important role of comprehensive rehabilitation and a multidisciplinary approach in achieving optimal outcomes in orthopedic care.